1944
DOI: 10.2307/1538340
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Factors in the Maximal Growth of Tetrahymena

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1945
1945
1973
1973

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…High levels of threonine can substitute for seine for release of inhibition but threonine is not a growth rate stimulator. 9. Comparisons are made between the data in the literature on vertebrates and tho'se reported here on Tetrahymena.…”
Section: + + +mentioning
confidence: 88%
“…High levels of threonine can substitute for seine for release of inhibition but threonine is not a growth rate stimulator. 9. Comparisons are made between the data in the literature on vertebrates and tho'se reported here on Tetrahymena.…”
Section: + + +mentioning
confidence: 88%
“…The organism used in the present study was the ciliated protozoan Tetrahymena geleii W, which is the strain used in the previous studies on thiamine synthesis (Kidder and Dewey, 1942;1944). All work was done with pure (bacteria-free)…”
Section: Methodsmentioning
confidence: 99%
“…Very little growth occurred in the absence of the alfalfa extract and the addition of thiamine, riboflavin, pyridoxine, pantothenic acid, nicotinic acid, pimelic acid, z-inosital, uracil, or />-aminobenzoic acid either singly or in combination had no significant effect. Inasmuch as the heat-and alkali-treated alfalfa extract w r as certainly free of thiamine it was concluded that Tetrahymena could synthesize the thiamine required for its metabolic needs when supplied with Factor S. It was suggested that Factor S possibly acted as a catalyst necessary for the synthesis of the thiamine molecule.It was recognized that the alfalfa extract used contained Factors I and II (Dewey, 1941 ;1944) and we now know that the casein base contained Factor III (Kidder and Dewey, 1945a). This work was criticized by Hall and Cosgrove (1944) on the basis that the "vitamin-free" casein used for the base medium was not free of thiamine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a few years, other leaders, expanding the coverage of the whole area, emerged from laboratories around the world: in America, first Dewey, Elliott, Hetherington, Jahn, Lilly, Loefer, Pace, Phelps, Seaman, and Taylor, and then Blum, Browning, Buhse, Cameron, Conner, Ducoff, Dunham, Eichel, Frankel, Holz, Hutner, McCashland, McDonald, Miiller, Padilla, Scherbaum, Shrago, Slater, Stone, Sullivan, G. A. Thompson, Whitson, N. E. Williams, Wingo, Zimmerman, and others; in England, F. E. G. Cox, Curds, Kitching, Ryley, and Sleigh; in Czechoslovakia, Jirovec and colleagues; in Denmark, Zeuthen, Hamburger, Nilsson, Plesner, Rasmussen, and associates; in Japan, Watanabe and others. No historical survey should by-pass the importance of the early, thorough, and stimulating account of the biochemistry of Tetrahymena (essentially T. pyriformis) produced by the team of Kidder & Dewey (1951), a now classical work setting the stage for hundreds of subsequent studies-by the Amherst group and many others-of a nature more refined than ever before possible. The protozoologist Holz might well be mentioned here, also, as one of the principal leaders in tackling with ingenuity problems in the biochemistry and physiology of species of Tetrahymena other than T. pyriformis (see, for example, Holz, 1964, (1) The growth factor thioctic acid, known early in unidentified form (Dewey, 1944), was more precisely recognized and then chemically identified (at first under a variety of names, including protogen and a-lipoic acid) in several laboratories a few years later (see papers by Seaman, 1952;Slater, 1952;Stokstad et al, 1949). A lipoate of wide distribution in nature, it is required only by species of Tetrahymena and related ciliate genera.…”
Section: Early Work Landmarks and Leadershipmentioning
confidence: 99%